Digital Evaluation Of Islamic Education - Pebiola, Pebiola Rahmadani; Pebiola Rahmadani; Sriwardona, Sriwar Dona (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
In the era of advancing technology and industry, digital technology and social media have become crucial tools for individuals and Muslim communities to express their religious identities, share religious knowledge, and build social networks. This research identifies various forms of religious expression emerging on digital platforms, including blogs, vlogs, podcasts, and social media. The study employs a qualitative descriptive research method to gather diverse sources and analyze participatory and content-based digital Muslim practices. The findings indicate that digital technology has expanded the scope and forms of religious practices, allowing flexibility in worship and creating space for more inclusive discussions and interpretations of religion. These insights shed light on how Muslims adapt to technological changes and how digitalization influences the dynamics of religious expression in contemporary Muslim societies.